When money fails to talk: Unintended consequences of using monetary incentives to elicit sustainable behaviours - LEE, Michelle P. (Institutional Knowledge at Singapore Management University, 2022)
The use of monetary incentives or disincentives to influence consumers to adopt sustainable behaviours is a common tactic. Appealing to one's wallet may be seen as a quick and easy way to bring about sustainable behaviours, but there are situations in which its use can backfire and have the unintended effect of lowering sustainable behaviours directly or indirectly. In this chapter, we discuss three unintended consequences. First, the use of a monetary incentive can put a spotlight on the size of the incentive relative to the effort involved and overshadow other considerations for sustainable behaviours, such as moral ones. When that calculus is applied, an incentive can paradoxically lead to lower compliance than when no incentive is provided. Second, the mere presence or mention of money can prime a self-sufficient orientation, which leads to an inclination for independence and a disinclination towards collaborative or helpful behaviours. Given that the argument for sustainable behaviours is the idea that individuals are part of a larger ecosystem and individual behaviours have collective impact, having a self-sufficient orientation does not jibe well with sustainability. Finally, the presence of a monetary incentive can lead one to infer that the incentive, rather than one's underlying attitude, is the motivation for sustainable behaviours. This represents a forgone opportunity for building positive sustainability attitudes that have longer-term effects on behaviours. Similarly, knowing that others might infer the incentive to be the motivation might limit one's willingness to avail himself/herself of the incentive. The practical implications of the aforementioned effects for designing monetary incentive schemes to encourage sustainable behaviours are discussed.